The impact of job satisfaction, organisational commitment, work-life balance and pay and reward towards employees’ turnover intention - Ng, Kay Yau (2023)
Employee turnover is a critical issue for organisations, impacting productivity, performance and success. This study investigates how job-satisfaction, organisational commitment, work-life balance and pay and reward impact employees' intention to depart the workplace. This research utilized a quantitative methodology to collect employee data across various industries using a structured questionnaire distributed. A total of 323 participants took part, and data analysis techniques such as Pearson Correlation Analysis (PCA) and Multiple Linear Regression Analysis were applied on their responses. Job satisfaction had a negative correlation with turnover intentions, suggesting that those who are more content in their current jobs are less likely to resign. Furthermore, organisational commitment negatively correlated with turnover intentions, suggesting employees who feel strongly committed and passionately connected to their company will likely remain loyal in place. Besides that, work-life balance had a direct bearing on turnover intentions - those who believe their personal and work lives are well balanced are less likely to consider leaving their current position. Furthermore, pay and reward was found to have an inverse relationship to turnover intentions; employees who feel they receive fair and competitive salary won't consider making changes in employment status. This study's results highlight the significance of increasing job satisfaction, organisational engagement, work-life integration, fair pay and reward systems as a means of decreasing employee turnover intentions. Organisations can improve job satisfaction by providing supportive environments, offering recognition opportunities and creating growth opportunities; to foster organisational commitment efforts can include creating a positive organisation culture while encouraging employee participation and providing career advancement opportunities.